Differential Phenotypes of Myeloid-Derived Suppressor and T Regulatory Cells and Cytokine Levels in Amnestic Mild Cognitive Impairment Subjects Compared to Mild Alzheimer Diseased Patients - Le Page, Aurélie; Garneau, Hugo; Dupuis, Gilles; Frost, Eric H.; Larbi, Anis; Witkowski, Jacek M.; Pawelec, Graham; Fülöp, Tamàs (Frontiers in Immunology, 2017)
Alzheimer Disease (AD) is the most prevalent form of dementia, the exact cause of which is not known. However, neuroinflammation is believed to play an important role, and immune system parameters that might contribute to this are already different from healthy donors (HD) at the stage of Mild Cognitive Impairment (MCI). A network of immune regulatory cells including regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) is responsible for maintaining immune homeostasis, but there are very few data on these cells in AD. Here, we investigated the presence of these cells in the blood of people with MCI and mild AD in comparison with healthy age-matched controls. We also assessed several pro- and anti-inflammatory cytokines in the sera which can influence the development and activation of these cells. Intriguingly, we found significantly higher levels of both MDSCs and Tregs in MCI but not in AD patients, as well as higher serum IL-1β levels. Stratifying the subjects based on CMV serostatus, known to influence multiple immune measures, did not result in any change to these differences between MCI versus AD and HD. We suggest that the increase in MDCS and Tregs in MCI may have a beneficial role in modulating inflammatory processes, but that this mechanism has failed and has allowed disease progression in those patients with AD. This hypothesis requires testing in future studies.